The Role of International Media in Shaping Public Opinion on International Conflicts: A Study of Pakistani Youth on Israel-Palestine War - Ashraf, Amna; Ahmed, Suleman; Hassan, Ifra (Pakistan Languages and Humanities Review, 2025)
This paper explores the international media in the formation of perceptions held by the Pakistani youths on the issue of the Israel-Palestine dispute, with emphasis on the effect of international news stories on perceptions, emotionality, and the priority of the issues. The study, relying on the Framing Theory, Agenda-Setting and Second-Level Agenda-Setting, Critical Discourse Analysis, and Social Identity Theory, considers how young audiences negotiate, interpret, and challenge the portrayal of the conflict in the media. The qualitative research design has been used in the study, purposive sampling has been used, and semi- structured interviews were used to interview 14 students of the university aged between 18 and 29 years who are active consumers of international news via television, digital media, and social networks. Thematic analysis of the data provided has identified four predominant patterns, which are the powerful impact of humanitarian and conflict frames; the agenda-setting impact of a repeated visual and textual cue; the critical recognition of bias, language, and omission in Western and non-Western media; and the mediating role of religious, national, and humanitarian identities in creating emotional and political meaning. The results indicate that international media can influence the issue salience and moral positioning substantially, but the Pakistani youth are not passive observers because they critique, redefine, and at times deny the prevalent discourse. The research adds to the literature as it discusses the interaction of global media discourse and youth meaning- making in conflict situations. It suggests the enhancement of critical media literacy and promotion of diversified media coverage to provide alternative and balanced views on international conflicts.